Disparitas Implementasi Program Adiwiyata di Kota Tarakan: Analisis Integrasi Kurikulum Lingkungan, Partisipasi Siswa, dan Model Hybrid Berbasis Jenjang Pendidikan - Yogho Prastyo; Ermawaty Maradhy (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to examine the disparities in the implementation of the Adiwiyata program in Tarakan City, North Kalimantan, with a focus on environmental curriculum integration and student participation across educational levels (elementary, junior high, and senior high). The study used mixed methods with a sequential explanatory design. Quantitative data were collected through surveys, then further deepened through in-depth interviews, observations, and document analysis in eight Adiwiyata schools. The results show clear disparities across educational levels, namely that program effectiveness increases with school level. Curriculum integration and student participation at the senior high school level significantly influence program effectiveness (β = 0.52; p < 0.05), while at the elementary school level, implementation is still dominated by a physical-administrative approach with instructive student participation. Another finding is that most external school collaboration is more directed at meeting physical indicators and environmental image, rather than strengthening teachers' pedagogical capacity. This study concludes that the success of the Adiwiyata Program is strongly influenced by the suitability of implementation strategies to the characteristics of the educational level. Thus, the need for differential policies that emphasize strengthening teacher ecological literacy at the elementary level, developing meaningful student participation, and evaluating programs based on ecological impacts.